Evaluating the influence of anti-PD-1 immunotherapy combined with IMRT on thyroid dysfunction in nasopharyngeal carcinoma - Chen, Liqianqi; Li, Zihuang; Li, Xianming; Wu, Shihai; Gong, Long; Xu, Gang; Chen, Shanyi; Zhang, Yucong (Frontiers in Immunology, 2025)
BackgroundImmunotherapy represents a major breakthrough in malignant tumor treatment in recent years. Anti-PD-1 immunotherapy has significantly prolonged Event-free Survival (EFS) in Nasopharyngeal Carcinoma (NPC). However, its potent anti-tumor effects can also attack normal tissues and organs, leading to immune-related adverse effects (irAE), with the thyroid being one of the most commonly affected organs. This study aims to analyze the incidence and related factors of thyroid dysfunction in NPC patients receiving anti-PD-1 immunotherapy with/without Intensity-modulated radiotherapy (IMRT), and further explore whether radiotherapy interacts with thyroid immune-related adverse reactions.Methods108 NPC patients receiving immunotherapy combined with chemotherapy or chemoradiotherapy were retrospectively included. Data collected included smoking status, BMI, presence of thyroid nodules, staging, treatment modality, thyroid mean dose (Dmean), percentage of thyroid volume receiving more than x Gy, pituitary mean dose (Dmean), and TSH and FT4 levels per cycle. T-tests, rank-sum tests, multivariate logistic regression analysis, ROC curves, and Cox proportional hazards models were used to evaluate the effects of anti-PD-1 immunotherapy combined with chemoradiotherapy on thyroid function.ResultsPatients with pre-treatment smoking history, thyroid nodules, and cervical lymph node metastasis were more likely to develop thyroid dysfunction (P<0.05). During treatment, 81 patients developed varying degrees of thyroid dysfunction. Subclinical hyperthyroidism (33.9%) was most common in the immunotherapy plus chemoradiotherapy group, while subclinical hypothyroidism (23.9%) was most common in the immunotherapy plus chemotherapy group. Compared to the immunotherapy plus chemotherapy group, the immunotherapy plus chemoradiotherapy group showed higher incidence and severity of hyperthyroidism (median peak FT4 concentration: 19.11 pmol/L vs 16.21 pmol/L) (P=0.001). The immunotherapy plus chemoradiotherapy group showed lower incidence but increased severity of hypothyroidism compared to the immunotherapy plus chemotherapy group, though these differences were not statistically significant.ConclusionNPC patients with smoking history, thyroid nodules, and cervical lymph node metastasis have significantly increased risk of thyroid dysfunction when receiving anti-PD-1 immunotherapy combined with IMRT. The combination of anti-PD-1 immunotherapy and IMRT increases both the incidence and severity of thyroid dysfunction.